Research Article Quality of life after laparoscopic hysterectomy versus abdominal hysterectomy - Yasushi Kotani; Kosuke Murakami; Risa Fujishima; Akiko Kanto; Hisamitsu Takaya; Masao Shimaoka; Hidekatsu Nakai; Noriomi Matsumura (BMC, 2021)
Abstract Background Laparoscopic surgery has been described as a minimally invasive surgery. The purpose of this study is to clarify its minimal invasive features using a patient questionnaire on the postoperative quality of life (QOL) over various time periods following either laparoscopic hysterectomy (LH) or abdominal hysterectomy (AH) and to compare the results. Methods This study enrolled 28 patients who underwent total hysterectomy for uterine fibroids in 2012 (14 AH cases and 24 LH cases) were enrolled in this study. The 36-Item Short Form Survey (SF-36) questionnaire was completed on postsurgical day 3; weeks 1, 2, and 4; and month 6. The results were compared between the two groups. Results Patients who underwent LH scored significantly higher on physical functioning on postoperative day 3 and week 2; physical role and bodily pain on day 3 and week 1; general health on postoperative day 3, weeks 1, 2, and 4, and month 6; social functioning on day 3; and emotional role on day 3 and week 1. No significant differences were found between vitality and mental health at any time point or in the categories above at any other time point. Conclusions Postoperative QOL in LH cases was improved on day 3 and week 1; however, no significant differences between the LH and AH groups were found in most categories at week 4 and month 6. LH leads to superior short-term QOL early in the postoperative period relative to AH.